2003
DOI: 10.1007/s00405-002-0570-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of testosterone in the treatment of immune-mediated sensorineural hearing loss

Abstract: Testosterones have beneficial effects not only on the modulation of expression of autoimmunity of B/W mice, but on other unrelated models such as autoimmune thyroiditis as well. This study was performed to evaluate the effect of testosterone in the treatment of immune-mediated sensorineural hearing loss (IMSNHL). To induce IMSNHL, 29 female Wistar rats were sensitized with bovine inner ear antigen three times weekly. Fourteen of 29 rats were injected subcutaneously three times a week with 250 microg of testost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…A few previous studies investigated the effects of testosterone on auditory functions [12,13]. The effects of testosterone in the immunemediated sensorineural hearing loss rat models were suggested [12]. However, low level of testosterone did not change the auditory brainstem response and otoacoustic emissions in the UV-filter octyl methoxycinnamate-exposed rats [13].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A few previous studies investigated the effects of testosterone on auditory functions [12,13]. The effects of testosterone in the immunemediated sensorineural hearing loss rat models were suggested [12]. However, low level of testosterone did not change the auditory brainstem response and otoacoustic emissions in the UV-filter octyl methoxycinnamate-exposed rats [13].…”
Section: Discussionmentioning
confidence: 96%
“…To the best of our knowledge, the application of androgen antagonists and the exploration of their protective mechanisms in hearing loss have not been previously reported. A few previous studies investigated the effects of testosterone on auditory functions [12,13]. The effects of testosterone in the immunemediated sensorineural hearing loss rat models were suggested [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning androgens, immune-mediated sensorineural hearing loss (IMSNHL) has a particularly higher incidence rate in women, and testosterone exerts beneficial effects on the modulation of the expression of this autoimmunity [38]. Chang et al (2001) [39] showed that a group of mice treated with several subcutaneous injections of testosterone had better results than the IMSNHL control animals in relation to the degree of hearing loss (10 to 20 dB vs. 10 to 40 dB) and the incidence of hearing loss greater than 20 dB in the ABR results.…”
Section: Hearing and Sex Hormonesmentioning
confidence: 99%